Causal Link between Employment and Renewable Energy Consumption: Evidence from Nigeria - Lawan, Mukhtar Wakil; Gidigbi, Matthew Oladapo (The European Journal of Applied Economics, 2019)
The paper examined the causal link between employment and renew-able energy consumption in Nigeria for the period of 1991 to 2014 using annual time series data. The Toda-Yamamoto Granger Causal-ity approach was used for causal analysis and Johansen cointegration technique to verify the long-run relationship between model variables. The results supported the conservation hypothesis with unidirectional causality from employment to energy consumption, but no evidence of cointegration was established. The study recommends that Nigeria should review its energy policy in order to promote private investment in renewable energy projects towards finding a sustainable solution to help solve the energy crisis, create employment opportunities, and minimise environmental pollution peculiar to long-term use of fossil fuel.